Treatment options for children with multi-drug resistant tuberculosis. Issue 1 (2nd January 2023) - Bossù, Gianluca; Autore, Giovanni; Bernardi, Luca; Buonsenso, Danilo; Migliori, Giovanni Battista; Esposito, Susanna
ABSTRACT: Introduction: According to the latest report from the World Health Organization (WHO), approximately 10.0 million people fell ill with tuberculosis (TB) in 2020, 12% of which were children aged under 15 years. There is very few experience on treatment of multi-drug resistant (MDR)-TB in pediatrics. Areas covered: The aim of this review is to analyze and summarize therapeutic options available for children experiencing MDR-TB. We also focused on management of MDR-TB prophylaxis. Expert opinion: The therapeutic management of children with MDR-TB or MDR-TB contacts is complicated by a lack of knowledge, and the fact that many potentially useful drugs are not registered for pediatric use and there are no formulations suitable for children in the first years of life. Furthermore, most of the available drugs are burdened by major adverse events that need to be taken into account, particularly in the case of prolonged therapy. A close follow-up with a standardized timeline and a comprehensive assessment of clinical, laboratory, microbiologic and radiologic data is extremely important in these patients. Due to the complexity of their management, pediatric patients with confirmed or suspected MDR-TB should always be referred to a specialized center.